The Green Marketing Model in Umrah Bureaus: A Satisfaction-Based Approach - Suryawan, Ryan Firdiansyah; Maulina, Evaf; Setiawan, Edhie Budi; Septiano, Renil; Susilowati, Tri (Yayasan Riset dan Pengembangan Intelektual, 2024)
Intense competition among umrah service providers in Jakarta and Bogor emphasizes the importance of effective digital marketing as well as a focus on consumer trust, service quality, and green marketing initiatives to increase e-loyalty. This study aims to analyze the effect of green marketing, consumer trust, and service quality on e-loyalty with customer satisfaction as an intervening variable. Data were collected from 150 umrah service users at five umrah bureaus in Jakarta and Bogor using purposive sampling method. Partial Least Square Structural Equation Model (SEM-PLS) 3.0 was used for data processing and testing. The results showed that green marketing, consumer trust, and service quality have a positive and significant effect on e-loyalty, both directly and through customer satisfaction as a mediator. Interestingly, although green marketing and consumer trust have a positive influence on customer satisfaction, service quality does not have a significant impact on satisfaction. This research highlights the importance of targeted digital marketing strategies and efforts to build consumer trust to increase loyalty in the umrah service sector.